Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1371/journal.pone.0078599
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chemotherapy for Childhood Leukemia on Brain Morphology and Function

Abstract: ObjectiveUsing multidisciplinary treatment modalities the majority of children with cancer can be cured but we are increasingly faced with therapy-related toxicities. We studied brain morphology and neurocognitive functions in adolescent and young adult survivors of childhood acute, low and standard risk lymphoblastic leukemia (ALL), which was successfully treated with chemotherapy. We expected that intravenous and intrathecal chemotherapy administered in childhood will affect grey matter structures, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(94 citation statements)
references
References 36 publications
5
85
0
3
Order By: Relevance
“…[2][3][4][5] However, these therapies are associated with substantial acute and long-term neurotoxicity. [6][7][8][9] Moreover, CNS relapse remains a major therapeutic obstacle in ALL, accounting for 30% of the relapses. [10][11][12][13][14][15] Despite its clinical importance, little is known about the mechanisms that cause CNS leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] However, these therapies are associated with substantial acute and long-term neurotoxicity. [6][7][8][9] Moreover, CNS relapse remains a major therapeutic obstacle in ALL, accounting for 30% of the relapses. [10][11][12][13][14][15] Despite its clinical importance, little is known about the mechanisms that cause CNS leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…(Von der Weid,2001; Langer et al,2002; Hill et al,2004; Spiegler et al,2006; Mahone et al,2007; Aukema et al,2009; Kadan-Lottick et al,2009; Kadan-Lottick et al,2010; Robinson et al,2010; Daams et al,2012; Krawczuk-Rybak et al,2012; Edelmann et al,2013; Genschaft et al,2013; Krull et al,2013; Lewis et al,2013; Ross et al,2013; Schuitema et al,2013; Edelmann et al,2014; Elalfy et al,2014) There were only 4 longitudinal studies that evaluated survivors’ neurocognitive changes from active treatment to post-treatment survivorship phase. (Kingma et al,2001; Harila et al,2009; Halsey et al,2011; Lewis et al,2013) Most studies focused on a pure sample of survivors who received chemotherapy-only treatment protocols while others included separate populations of ALL survivors who received CRT(Kingma et al,2001; Von der Weid,2001; Langer et al,2002; Spiegler et al,2006; Harila et al,2009; Kadan-Lottick et al,2010; Halsey et al,2011; Krull et al,2011; Daams et al,2012; Krull et al,2013; Schuitema et al,2013; Edelmann et al,2014) or patients of other cancer types.…”
Section: Resultsmentioning
confidence: 99%
“…(Kingma et al,2001; Harila et al,2009; Halsey et al,2011; Lewis et al,2013) Most studies focused on a pure sample of survivors who received chemotherapy-only treatment protocols while others included separate populations of ALL survivors who received CRT(Kingma et al,2001; Von der Weid,2001; Langer et al,2002; Spiegler et al,2006; Harila et al,2009; Kadan-Lottick et al,2010; Halsey et al,2011; Krull et al,2011; Daams et al,2012; Krull et al,2013; Schuitema et al,2013; Edelmann et al,2014) or patients of other cancer types. (Aukema et al,2009; Kadan-Lottick et al,2010) The majority of the included studies had sample sizes between 10 to 50 subjects,(Kingma et al,2001; Langer et al,2002; Hill et al,2004; Mahone et al,2007; Aukema et al,2009; Harila et al,2009; Daams et al,2012; Krawczuk-Rybak et al,2012; Edelmann et al,2013; Genschaft et al,2013; Schuitema et al,2013; Edelmann et al,2014) with the exception of 4 studies with a larger cohort of more than 100 subjects(Von der Weid,2001; Kadan-Lottick et al,2010; Halsey et al,2011; Krull et al,2013) and 3 studies with less than 10 subjects. (Lewis et al,2012; Lewis et al,2013; Ross et al,2013) Most the studies reported survivors’ mean duration of time since diagnosis, which ranged between 5 and 22 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study by Edelmann et al (2014) in slightly older ALL survivors demonstrated a primarily left lateralized profile of alterations in FA in comparison between chemotherapytreated patients and healthy controls. Given that others have shown bilateral alteration of FA (Morioka et al, 2013) as well as no group differences in FA (Genschaft et al, 2013), the significance, if any, of left lateralized findings remains unclear. However, increased left hemisphere susceptibility has been consistently noted in several other neurological conditions.…”
Section: Discussionmentioning
confidence: 95%